PREPARASI FILM NANOKOMPOSIT POLIVINIL ALKOHOL (PVA)/NANOKARBON DARI CANGKANG BUAH SAWIT (NCCS) DENGAN METODE PENCAMPURAN LARUTAN - Purwandari, Vivi; Tarigan, Malemta (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2022)
Polyvinyl alcohol (PVA) has good compatibility when added as filler in the form of nanocarbon so that it can produce environmentally friendly nanocomposite products. Thus, the addition of nanocomposites to PVA-based films is expected to increase and improve the mechanical properties of the resulting PVA films. This study aims to utilize palm fruit shells as raw materials for nanocarbons and as fillers for nanocomposites, as well as to determine the mechanical properties and thermal strength of nanocarbon nanofibers in the PVA matrix. Composite films were made using the solution mixing method. The research was conducted by mixing PVA solution (3.5 g) with various concentrations of nanocarbon from palm fruit shells (NCCS) and 2 ml of glycerol and 1 g of PEG 400. Film characterization includes tensile test, scanning differential calorimetry (DSC), and conductivity test. Tensile test of PVA/NCCS nanocomposite resulted in tensile strength of 0.314 MPa and an elongation of 4.21925 %. The thermal test of PVA/NCCS nanocomposite with DSC yielded a melting point of around 146.06oC. Electrical conductivity of PVA/NCCS 107.1 (1.07 x 10-3) s/cm. PVA/NCCS nanocomposite based on conductivity scale including a semiconductor material.